Realization of a communicative approach in the process of learning a foreign language - Volkova, Liudmyla Viktorivna (ВГ Наукові перспективи, 2022)
The importance of forming foreign language communicative competence in the context of professional training has been ascertained for efficient usage in learning process of foreign language. The efficiency of communicative aspect in the educational process of higher education is proved, as it provide an opportunity to form professional skills of future professionals, involving them in intensive cognitive, intellectual and creative activity.Communicative activity is considered as a process of solving a number of professional tasks by students. This activity is aimed at achieving a common goal - training, education and personal development of a student. The aim of the communicative activity is the formation of foreign language communicative competence using of the theoretical material in solving professional problems. The importance of understanding the main structural elements of communicative activity have been ascertained for its efficientusage in learning process of foreign language.The article highlights the problems associated with different methods and techniques of communicative-based learning. The communicative activity approach of learning foreign languages is particular important. It is based on the fact that learning is a model of communication. The basic principles of its implementation as a communicative teaching method of speaking are analyzed.It should be noted that communicative and active approach to learning foreign languages is one of the most significant and effective. Through communicative methods, lessons can be more interesting and various. This means that students will have interest in further understanding and learning. Communicative nature of communication is that learning is a model of the communication process.Communicative orientation of learningprocess is a prerequisite of success in practical learning of a foreign language.Communicative activity approach is based on the fact that learning is a model of communication. The communicative method of teaching activities is based on the main principles which are analyzedbelow.to create a space of diversity in education are described.

У статті доведено важливість формування іншомовної комунікативної компетенції у контексті професійної підготовки майбутніх фахівців, розглядаються умови ефективної реалізації комунікативного підходу у процесі вивчення іноземної мови. У статті висвітлюються проблеми, пов’язані із різними методами та прийомами реалізації комунікативно-орієнтованого навчання. Особливого значення набуває комунікативно-діяльнісний підхід до вивчення іноземних мов, який базується на тому, що процес навчання є моделлю комунікації. Розглядаються основні принципи його реалізації як комунікативного методу навчання мовленнєвої діяльності. Комунікативно-орієнтоване навчання можливе лише за умов діяльнісного підходу. Слід зазначити, що комунікативно-діяльнісний підхід до вивчення іноземних мов є одним із найбільш значущих і ефективних. Завдяки комунікативним методам заняття можуть бути цікавими та різноманітними. Комунікативна спрямованість процесу навчання є передумовою успішності практичного вивчення іноземної мови. У статті розглядаються принципові положення організації процесу комунікативного навчання. Комунікативно-орієнтоване навчання іноземних мов можливе в умовах автентичного процесу соціалізації студентів. Проблема навчання студентів університету професійно-орієнтованого спілкування іноземною мовою є важливим компонентом навчальної діяльності, який стимулює формування навичок та умінь іншомовної професійно-орієнтованої комунікації. Передбачається вільне володіння студентами іноземною мовою та здатність формувати ними нові знання на основі існуючих знань та різних когнітивних процесів. Саме сучасні вимоги до вищої освіти обґрунтовують використання комунікативно-діяльнісного підходу до викладання іноземних мов. Особливе місце в процесі навчання студентів займає мотивація, яка сприяє підвищенню ефективності та результативності навчального процесу у вищому навчальному закладі.
Реалізація комунікативного підходу у процесі вивчення іноземної мови
Keywords: foreign language communicative competence; professional training; communicative method; learning process of foreign language; іншомовна комунікативна компетенція; професійна підготовка; комунікативний підхід; вивчення іноземної мови